1998
DOI: 10.1590/s0100-879x1998000100007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th1 and Th2 cells in autoimmune demyelinating disease

Abstract: Evidence is accumulating that Th1 cells play an important role in the development of multiple sclerosis (MS) and experimental allergic encephalomyelitis (EAE), whereas Th2 cells contribute to recovery from disease. A major determinant in the development of Th1 and Th2 cells is the type of antigen-presenting cell (APC) involved and its functional characteristics, e.g., the production of interleukin-12. Therefore, modulation of APC might interfere with the development of Th1 type responses and as such be benefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Recent studies have indicated that Th17 cells and IFN-γ-secreting Th1 cells play an important role in the clinical pathogenesis in EAE/MS disease (Komiyama et al, 2006; Nagelkerken, 1998; Segal, 2003; Skarica et al, 2009; Yura et al, 2001). In addition, proinflammatory cytokines such as TNFα and IL-6 are also considered important for induction and pathogenesis involving inflammation and neuroglial damage (Penkowa and Hidalgo, 2001; Villarroya et al, 1997; Wiemann et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have indicated that Th17 cells and IFN-γ-secreting Th1 cells play an important role in the clinical pathogenesis in EAE/MS disease (Komiyama et al, 2006; Nagelkerken, 1998; Segal, 2003; Skarica et al, 2009; Yura et al, 2001). In addition, proinflammatory cytokines such as TNFα and IL-6 are also considered important for induction and pathogenesis involving inflammation and neuroglial damage (Penkowa and Hidalgo, 2001; Villarroya et al, 1997; Wiemann et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The rapid activation of both a TH1 and TH2 response in fetal brains exposed to intrauterine LPS observed in this study suggest that these responses play an early and crucial role in preterm brain injury. Prolonged activation of a TH1 response is implicated in white matter damage in active inflammatory states within the CNS (31). In contrast, TH2 cytokines or agents that augment a TH2 response have been demonstrated to ameliorate disease progression (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Given the key role of STAT1 in the development of T H 1 cells, which are implicated in the onset of EAE, compared with T H 2 cells that promote recovery from the disease, the inhibition of IFNγ-dependent STAT1 activation could be used as a means to normalize the T H 1–T H 2 balance and promote recovery from the EAE phenotype 145,146 .…”
Section: Inhibitors Of Stat1 and Stat4mentioning
confidence: 99%